أدب الرحلة في اللغة العربية وتأثيره على الوضع الاجتماعي والسياسي والاقتصادي والديني: Traveling literature in Arabic language & its impact upon the social, political, economic and religious status - د. حافظ محمد بادشاہ; د. أمین علی (JAR, 2022)
Travel literature includes many literary genres, such as: history, story, rhetoric, and poetry, and with the abundance of transportation and its speed, the world has become a small village, and this has directly affected the travel literature. Travel literature is a type of literature based on the description of the writers of what he witnessed in his travels, such as urbanization, events, people, customs, traditions, and others things. Travel literature is a kind of living literature that grows with the passage of ages in different colors, with different motives and purposes. It may be for a religious, economic, scientific, cultural, political, tourism, health or purely entertainment purpose. With the multiplicity of purposes of travels and the diversity of their motives, travels are colored in many shapes. Is there any effect between travel literature and between sociology, politics, economics and religion, or not? So, Travel literature is live literature that affects and is affected. We find a golden chain of history that travel literature has affected the human conditions and the environment. Commercial travels, Hajj and Umrah travels, travels for medical purposes, and Orientalist travels for various purposes are evidences and examples of the impact of travel literature on situations and circumstances.